PELATIHAN PEMBUATAN SELAI KACANG TANAH DI KAMPUNG GWINJAYA DISTRIK BONGGO KABUPATEN SARMI, PAPUA - Zebua, Lisye I.; Budi , I Made; Gunaedi, Tri; Rahayu , Irma; Asnawi , Meinarni; Triwiyono , Triwiyono; Numberi, Anastasia (LPPM Uncen, 2024)
Gwinjaya Village in Bonggo District is one of the peanut commodity center areas. The problem is that the low selling value causes the income of peanut farmers to remain low so that peanut commodities have not been able to improve the welfare of the Gwinjaya community, and the lack of information about the diversification of peanut-based preparations in Gwinjaya Village. The specific objectives of this service activity are to introduce processed peanut-based agricultural products that have high selling value to the people of Gwinjaya Village in Bonggo district and train people in Gwinjaya Village on how to make jam from peanuts, as well as how to package it. The service method used in this training consists of three stages, namely lectures, discussions, and practices. The results and achievements of this service activity are that the community can produce nutritious and economically valuable peanut jam products. Based on the results of organoleptic tests on peanut butter products, the taste, aroma, and color criteria are in the mildly liked category, while the texture criteria are in the liked category.